Entrepreneurial Mentality Analysis for College Students Based on the Improved BP Neural Network. (9th August 2022) - Fan, Jinling
Abstract : In this study, the fuzzy comprehensive evaluation model is used to evaluate the characteristics of college students' entrepreneurial psychology, and a prediction model of college students' entrepreneurial psychology characteristics is established, which is simulated by Matlab to achieve good validity. Based on the research on the characteristics of college students' entrepreneurial psychology, this study proposes a design method of indicators and parameters for evaluating the characteristics of college students' entrepreneurial psychology. In this study, the genetic algorithm is used to optimize the BP neural network. The optimized neural network greatly improves the global search and local search capabilities. The performance of the model is tested through simulation tests. Through the simulation comparison test between the improved model and the standard model, the results show that the model can predict the entrepreneurial psychological characteristics of college students. By comparing the improved BP neural network algorithm with the original algorithm simulation experiment, the improved BP neural network improves the sensitivity by 20%, the specificity by 5%, and the accuracy by 8%.